Polygamy Marriage: Legal Culture, Optional Political Identity And Marital Status Dilemma (A Case Study in Pekalongan) - Shinta Dewi Rismawati; Muhammad Abral Bin Abu Bakar (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2019)
Polygamy allowed but with strict conditions. In this paper, I argue that the legal culture of polygamous marriage perpetrators is not solely influenced by the tight laws on polygamy but also other non legal factors, diverse legal cultures which directly affect on the diverse legal status of the perpetrators and children born in the marriage. Therefore, the paper scrutinized why the actors’ legal culture in carrying out their polygamy marriage were negative and how the legal status and implications of the polygamous marriages to the marriages held by themselves and their children. The research method of social legal studies was used as the approach. The findings and analysis show how hard the actors met the requirements of the legal provisions on polygamy which are only one reason to justify it. In other hand, it was found that the non-legal dimensions were very complex and also influential so that the legal culture was negative. Consequently, polygamous marriage in siri was a political choice of their lives. It has the implications on the legal status of polygamous marriages and the perpetrators. The marital status is deemed to exist when the marriage is performed officially; and it is considered non-existent when the marriage is performed in siri. Polygamous marriage also has an impact on the legal status of the husband, his second wife, and their children in the family.